Предмет: Математика,
автор: Аноним
все примеры по действиям
Приложения:
![](https://files.topotvet.com/i/2fb/2fb5b0da400425469a79bf50af73701d.jpg)
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
1)-3(4х-2)+1=-5
-3×4х-3×(-2)+1=-5
-12х+6+1=-5
-12х=-5-6-1
-12х=-12
х=-12÷(-12)
х=1
2)6+2(-5х+3)=2х+48
6+2×(-5х)+2×3=2х+48
6-10х+6=2х+48
6+6-48=2х+10х
12-48=12х
-36=12х
х=-36÷12
х=-3
Похожие вопросы
Предмет: Литература,
автор: roster1
Предмет: Русский язык,
автор: KateYak2002
Предмет: Русский язык,
автор: anastasia018
Предмет: История,
автор: Marenna
Предмет: Математика,
автор: ex773643